Efficacy and safety of low-dose esketamine for painless gastrointestinal endoscopy in adults: a systematic evaluation and meta-analysis - Deng, Juan; Yu, Yun-Feng; Tang, Zheng-Guo; Lei, Hua-Juan; Tan, Chuan-Chuan (Frontiers in Pharmacology, 2024)
The benefits of low-dose esketamine for painless gastrointestinal endoscopy remain unclear.As such, the present study aimed to investigate the efficacy and safety of low-dose esketamine for this procedure.Methods: Seven common databases were searched for clinical studies investigating low-dose esketamine for painless gastrointestinal endoscopy. Subsequently, a meta-analysis was performed to synthesize and analyze the data extracted from studies fulfilling the inclusion criteria.Results: Meta-analysis revealed that, compared with propofol, low-dose esketamine in combination with propofol significantly reduced recovery time by 0.56 min (mean difference [MD] -0.56, 95% confidence interval (CI) -1.08 to -0.05, P=0.03), induction time by 9.84 s (MD -9.84, 95%